SOYBEAN BREEDING FOR TOLERANT TO DROUGHT DURING REPRODUCTIVE STAGE - Suhartina Suhartina (Buletin Palawija, 2022)
One of the strategies to increase soybean production in Indonesia is maximizing the use of rainfed lowland or dry land using varieties having characters of drought tolerant, high yielding, early maturing and resistant to biotic stress. The Ministry of Agriculture of the Republic of Indonesia has released six soybean varieties tolerant to drought during the reproductive stage, namely  Dering 1, Dering 2 and Dering 3 varieties which are yellow seeds, while the Detam 2, Detam 3 and Detam 4 varieties are black seeds.Among these six varieties, the Dering 1, Dering 2, Dering 3, and Detam 4 varieties showed a tolerant response to drought, while Detam 2 and Detam 3 showed an intermediate tolerant response. Dering 2 variety showed the highest seed yield potential of 3.32 tons/ha. Dering 1 and Dering 3 varieties showed aresistant response to pod borer. There was no variety showed a resistant response to pod armyworm pest. Dering 3 variety showed a resistant response to both pod borer and pod sucking. For resistance to leaf rust, only Dering 1 showed a resistant response. Dering 1 variety showed a resistant response to both pod borer and leaf rust.Dering 1, Dering 2, Dering 3, and Detam 4 varieties could be recommended to be planted in rainfed  lowland or dry land areas  during dry season-2 where rainfall is limited.